Timing of international market entry of UK and German high-tech start-ups - Oliver Bürgel; Andreas Fier; Georg Licht; Gordon Murray (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
We examine the impact of technological product advantages, prior international experience of the management, firm size and age, country differences, and sunk costs as determinants of the timing of international market entry. The timing of internationalisation is analysed using ?event history analysis? for 600 British and German start-up companies in high-technology industries. The results indicate that the incidence of internationalization increases over time. For the majority of new firms the question is not whether the firm will internationalize but when. The analyses indicated that a high commitment to R&D fosters rapid internationalization. The involvement of founder managers who are internationally experienced increases the speed of foreign market activity. Working against rapid internationalization was a high level of product customization. The findings suggest that timing of internationalization is a dynamic process which is influenced by initial human capital endowment, technological advantages, and learning from of day to day activities.
Keywords: L21; F23; L60; 330; start-ups; high-technology industries; internationalisation; Hochtechnologiesektor; Unternehmensgründung; Internationale Markteintrittsstrategie; Zeit; Schätzung; Großbritannien; Deutschland